Serviço social e comunidades : experiências de atuação e perspectivas de re(atualização) crítica - Botelho, Thaynara Moreira (2016)
This dissertation materializes to analyze experiences of social worker performance in community of Brazil since fifties in the twentieth century. For this reason, it used the qualitative method marked in Marxism and based in bibliographic search. The ramifications of this study were structured since the community experiences that had premodern trace until experiences marked in struggle for social rights in a moment of structural crisis of capital. In the current historic time, the merchandise producer system got into unable limit of its existence. In this way, the capacity of social politics financing to capitalism orders also fell into crisis. Before women and men necessity to find way of survival in the social barbarism context, the alternative struggles and resistance options are forming out of institutionalized way. The analysis of the historical development of the Social Work performance with community and spontaneus experiences (that had pre-modern traces) until consolidation of institutionalized and modernized experiences in the dictatorial period and after it, permit us thinking in professional practice alternative beyond guarantee of our rights. Therefore, with the historic limits of capitalism production, people (no more lucrative to the capitalism) may find way of resistance that transcend the system itself. For this reason, there is need to reflect about the work of Social Worker with communities to not interrupt the experiences produced by people in the historic moment of "social barbarism".